Clinical anatomy of the anterior and posterior hepatic plexuses, including relations with the pancreatic plexus: A cadaver study. Issue 5 (12th October 2019) - Ren, Ke; Yi, Shuang‐Qin; Dai, Yidan; Kurosawa, Kazuhiro; Miwa, Yoko; Sato, Iwao
Abstract : The poor prognosis after surgery for pancreatic cancer or extrahepatic bile duct cancer has mainly been attributed to early lymph node metastasis, as well as a high frequency of perineural invasion along the peripancreatic neural plexuses or extrahepatic bile duct plexus. However, there has been no detailed morphological description of the anterior and posterior hepatic plexuses (AHP and PHP). In addition, the concepts of the pancreatic plexus and PHP are confused by surgeons. To assess the relations of the pancreatic plexus and hepatic plexuses from the morphological, developmental, and clinical perspectives, these plexuses were dissected in 24 cadavers. The PHP was found to be completely independent of the AHP. The PHP ran behind the portal vein, with most nerve fibers ascending along the bile duct to the gallbladder and the liver or descending to the distal common bile duct and duodenal papilla. Some branches of the PHP contributed to the pancreatic plexus, corresponding to pancreatic head plexus I as defined by the Japan Pancreas Society. The differences between the PHP and pancreatic head plexus I should be understood, even though liver function is not obviously affected after PHP excision for pancreatic head cancer. Further study is needed to determine whether there are functional differences between the AHP and PHP. Clin. Anat., 33:630–636, 2020. © 2019 Wiley Periodicals, Inc.